A Methodology To Evalute Design Efficiency Based On Assembly Criteria In Support Of Design For Modularity. - Abdullah, Ahmad Baharuddin; Mohd Ripin, Zaidi; Mokhtar, M (Institute of Emergency Management., 2005)
Companies are striving to produce high quality and reliable product at the lowest cost to remain competitive in the market.